Safety and tolerability of the β3‐adrenoceptor agonist mirabegron, for the treatment of overactive bladder: results of a prospective pooled analysis of three 12‐week randomised Phase III trials and of a 1‐year randomised Phase III trial. Issue 8 (6th April 2014) - Nitti, V. W.; Chapple, C. R.; Walters, C.; Blauwet, M. B.; Herschorn, S.; Milsom, I.; Auerbach, S.; Radziszewski, P.
Summary Aims To evaluate the safety and tolerability of the β3‐adrenoceptor agonist, mirabegron, in patients with overactive bladder (OAB). Methods Tolerability and safety data from three 12‐week, randomised, placebo‐controlled, double‐blind, Phase III trials (Studies 046, 047 and 074) were pooled by treatment group. The three studies were of a similar design, although the assessed doses of mirabegron [25, 50 or 100 mg once daily (qd)] varied, and tolterodine extended release (ER) 4 mg was included as an active‐control arm in Study 046 only. Tolerability and safety data from a 1‐year, randomised, double‐blind, Phase III trial (Study 049) are also presented. Safety variables included the incidence and severity of treatment‐emergent adverse events (TEAEs), vital signs and electrocardiogram data. Results Mirabegron (25, 50 or 100 mg qd) was safe and well‐tolerated in patients with OAB over 12‐week (n = 2736) and 1‐year (n = 1632) periods. The incidence of TEAEs and treatment discontinuations as a result of TEAEs was low; the majority were mild in severity and few were serious. Hypertension, nasopharyngitis and urinary tract infection were the most common TEAEs with mirabegron. The mirabegron tolerability profile was similar to that seen with placebo and tolterodine ER 4 mg, except for dry mouth, which occurred, on average, five times less frequently with mirabegron than tolterodine ER 4 mg. In the pooled 12‐week analysis, mirabegron 50 mg was associated with placebo‐adjusted mean increases of 0.4–0.6 mmHg in blood pressure and approximately one beat per minute in pulse rate, both reversible upon treatment discontinuation. The incidence of Major Adverse Cardiovascular Events as adjudicated by an independent cardiovascular committee was low and similar across treatment groups. Conclusion The favourable tolerability profile of mirabegron in patients with OAB may allow improved treatment compliance compared with antimuscarinics, with important implications for patient outcomes.